2011
DOI: 10.1002/lsm.21102
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of disseminated non-small cell lung carcinoma in a murine model

Abstract: Background and Objective Photodynamic therapy (PDT) of thoracic malignancies involving the pleural surfaces is an active area of clinical investigation. The present report aims to characterize a model for PDT of disseminated non-small cell lung carcinoma grown orthotopically in nude mice, and to evaluate PDT effect on tumor and normal tissues. Study Design H460 human non-small cell lung carcinoma (NSCLC) cells were injected percutaneously into the thoracic cavity of nude mice. HPPH-PDT (1 mg/kg, 24 h) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Fluence rate effects of intrathoracic PDT were investigated in our previously described murine model [ 24 ]. Disease was propagated by the percutaneous injection of H460 cells in the thoracic cavity and developed as disseminated bilateral intrathoracic masses that visibly ranged from pinpoint to mm-sized nodules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluence rate effects of intrathoracic PDT were investigated in our previously described murine model [ 24 ]. Disease was propagated by the percutaneous injection of H460 cells in the thoracic cavity and developed as disseminated bilateral intrathoracic masses that visibly ranged from pinpoint to mm-sized nodules.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies reported here, we evaluated fluence rate effect on EGFR activation in tumor nodules of the PDT-treated murine thoracic cavity. Human tumor xenografts of non-small cell lung carcinoma (NSCLC) were grown as disseminated disease in the murine thoracic cavity [ 24 ]. In contrast to a single nodule of disease at either a subcutaneous or orthotopic site, our intrathoracic model recapitulates the multinodular and diffuse spread of pleural malignancies that are treated in clinical trials of pleural PDT.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is circumvented by using bioluminescence imaging, computed tomography (CT), and magnetic resonance imaging (MRI) (Grossman et al, 2011; Mordant et al, 2011; Justilien et al, 2012; Liu et al, 2012; Madero-Visbal et al, 2012;). Lung orthotopic tumors formed by cancer cells transduced to express the firefly luciferase gene can be monitored for progression, invasion, and metastasis in vivo using the IVIS Spectrum imaging device and associated protocols.…”
Section: Basic Protocol: Orthotopic Nsclc Mouse Modelmentioning
confidence: 99%
“…As visible light depth penetration within biological tissues is limited to few millimeters [16], external illumination are mostly dedicated to superficial lesions or in vitro studies. External illuminations can be performed in intracavitary locations with optical fiber devices (panels, balloons or cylindrical diffuser) [12,[17][18][19][20][21] and in topical locations with frontal end optical fibers, LASER beams or LED panels [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%